2014
DOI: 10.1111/sapm.12066
|View full text |Cite
|
Sign up to set email alerts
|

Quicksilver Solutions of a q‐Difference First Painlevé Equation

Abstract: In this paper, we present new, unstable solutions, which we call quicksilver solutions, of a q‐difference Painlevé equation in the limit as the independent variable approaches infinity. The specific equation we consider in this paper is a discrete version of the first Painlevé equation (qPI), whose phase space (space of initial values) is a rational surface of type A7(1). We describe four families of almost stationary behaviors, but focus on the most complicated case, which is the vanishing solution. We derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…By applying w to (5.26), we have 42) which give the precise form of w( f ) and w(g) observed in (5.5).…”
Section: τ Functionsmentioning
confidence: 99%
“…By applying w to (5.26), we have 42) which give the precise form of w( f ) and w(g) observed in (5.5).…”
Section: τ Functionsmentioning
confidence: 99%
“…Motivated by Boutroux's study of the first Painlevé equation [7], the asymptotic behaviour of (1) in the limit |x| → ∞ has been considered in [28,30]. Joshi [28] showed that there exists a true solution satisfying w → 0 as |x| → ∞, which is asymptotic to a divergent series. However, [28] does not describe the Stokes switching behaviour that is typically associated with (divergent) asymptotic series.…”
Section: Introductionmentioning
confidence: 99%
“…Joshi [28] showed that there exists a true solution satisfying w → 0 as |x| → ∞, which is asymptotic to a divergent series. However, [28] does not describe the Stokes switching behaviour that is typically associated with (divergent) asymptotic series.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations